Pengaruh Perbandingan Mocaf Dan Tepung Kacang Hijau (Vigna radiata) Terhadap Karakteristik Pancake - Einsteina Michelle Olga; Putu Ari Sandhi Wipradnyadewi; Anak Agung Istri Sri Wiadnyani (Itepa : Jurnal Ilmu dan Teknologi Pangan, 2026)
Increasing public awareness of the importance of a healthy diet encourages the development of gluten-free pancakes using modified cassava flour (mocaf). The protein content of pancakes can be enhanced by adding mung bean flour, which is rich in plant-based protein. This study aimed to determine the effect of the ratio of mocaf to mung bean flour on the characteristics of pancakes. The research employed a Completely Randomized Design (CRD) with six treatment ratios of mocaf and mung bean flour (100:0, 85:15, 70:30, 55:45, 40:60, and 25:75), with three replications. The observed parameters included moisture content, protein content, crude fiber content, fat content, ash content, carbohydrate content, hardness, and sensory evaluation (color, aroma, taste, texture, softness and chewiness, beany odor, and overall acceptability). The data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT). The results showed that the ratio of mocaf and mung bean flour significantly affected the pancake characteristics. The best pancake characteristics were obtained at the ratio of 25% mocaf:75% mung bean flour, with moisture content of 37.20%, protein content of 24.98%, crude fiber content of 7.53%, ash content of 2.93%, fat content of 6.90%, carbohydrate content of 32.06%, hardness of 1.53 N, and sensory scores indicating a “like” category for color (overall color and color after cutting), aroma, and overall acceptability, while taste and texture were rated as “slightly like,” with a chewy and soft texture and a slightly beany odor.